Elevated levels of Lp(a) are associated with coronary lesion complexity in patients hospitalized for an acute myocardial infarction: data from the French RICO Survey. (3rd October 2022) - Kouame, I; Farnier, M; Chague, F; Maza, M; Bichat, F; Zeller, M; Cottin, Y
Abstract: Background: Although patients with elevated Lp(a) are at high risk of acute myocardial infarction (MI), coronary artery disease (CAD) burden associated with Lp(a) remains poorly investigated. Methods: Single center study including all consecutive patients hospitalized for an acute MI in Coronary Care Unit from the RICO database (2019–2021) who underwent coronary angiography and blood sample for Lp(a) assessment on admission. Coronary lesion complexity was retrospectively assessed by SYNTAX score and pre-specified angiographic criteria. Patients were compared according to their Lp(a) levels: <50 mg/dL (normal), ≥50 mg/dL and ≤100 mg/dL (high) and >100 mg/dL (very high). Results: 921 patients were included, of whom 177 (19.2%) had elevated Lp(a) >50 mg/dL, including 121 (13.1%) with high and 56 (6.1%) with very high Lp(a). Median (IQR) age was similar across the 3 groups (normal: 68 (58–78)y; high: 70 (60–80)y; very high: 69 (61–78)y, p=0.381). When compared with patients with normal Lp(a), patients with high and very high Lp(a) levels had increased prevalence of personal history of CAD (19%, 28% and 29%, respectively, p=0.026) and family history of CAD (19%, 26% and 29%, p=0.032, respectively). The rate of women was more common in very high Lp(a) level than in high and normal groups (46%, 33%, and 29%, respectively, p=0.016). Rate of ST-segment elevation MI was similar for the 3 groups (p=0.961). At coronary angiography, CAD burden, as assessed by SYNTAX score was much higher in elevated Lp(a) groups (11 (6–19), 15 (8–24), 17 (7–25), p=0.001, respectively). Moreover, patients with elevated Lp(a) had more complex coronary lesions (p=0.034), characterized by left main (p=0.021), and calcified lesions (p=0.002) (figure). In-hospital mortality gradually increased across the 3 groups (2.8%, 6.6%, 8.9%, p=0.010, respectively). Conclusions: This retrospective study in patients with acute MI shows that elevated Lp(a) were common, associated with high risk for in-hospital mortality. Patients with high Lp(a) were characterized by severe CAD burden, with complex anatomy features including left main and calcified lesions. The long-term prognostic impact of Lp(a)-associated CAD burden needs to be explored. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): ARS Bourgogne Franche ComtéCHU Dijon BourgogneAssociation de Cardiologie de Bourgogne